2006
DOI: 10.1523/jneurosci.1728-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Derived Factor-1 (Chemokine C-X-C Motif Ligand 12) and Chemokine C-X-C Motif Receptor 4 Are Required for Migration of Gonadotropin-Releasing Hormone Neurons to the Forebrain

Abstract: Gonadotropin-releasing hormone (GnRH) neurons migrate from the vomeronasal organ (VNO) in the nasal compartment to the basal forebrain in mice, beginning on embryonic day 11 (E11). These neurons use vomeronasal axons as guides to migrate through the nasal mesenchyme. Most GnRH neurons then migrate along the caudal branch of the vomeronasal nerve to reach the hypothalamus. We show here that stromal cell-derived factor-1 [SDF-1, also known as chemokine C-X-C motif ligand 12 (CXCL12)] is expressed in the embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 36 publications
5
61
0
3
Order By: Relevance
“…Thus, the temporal-and region-specific aspects of receptor variability, as impacted by either genetic or epigenetic factors, may have dissociable effects on psychiatric disease risk at different points of the life course, adding a layer of complexity to our understanding of psychiatric risk alleles. This is consistent with findings in multiple systems where a particular molecule has a different role during development compared with adulthood (Laurent et al, 2002;Schwarting et al, 2006;Young-Davies et al, 2000). For example, serotonin transporter blockers such as fluoxetine appear to have opposite effects during development, where they increase anxiety, than in adulthood, where they decrease anxiety (Ansorge et al, 2004).…”
Section: -Ht1a-mediated Anxiety Phenotypes Are Developmental In Originsupporting
confidence: 91%
“…Thus, the temporal-and region-specific aspects of receptor variability, as impacted by either genetic or epigenetic factors, may have dissociable effects on psychiatric disease risk at different points of the life course, adding a layer of complexity to our understanding of psychiatric risk alleles. This is consistent with findings in multiple systems where a particular molecule has a different role during development compared with adulthood (Laurent et al, 2002;Schwarting et al, 2006;Young-Davies et al, 2000). For example, serotonin transporter blockers such as fluoxetine appear to have opposite effects during development, where they increase anxiety, than in adulthood, where they decrease anxiety (Ansorge et al, 2004).…”
Section: -Ht1a-mediated Anxiety Phenotypes Are Developmental In Originsupporting
confidence: 91%
“…Many studies suggest that tumor cell migration and organspecific metastasis are critically regulated by chemokines and their receptors (21)(22)(23)(24)(25)(26)(27)(28)(29). The axis of CXCR4/CXCL12 plays an important role in metastasis of many tumors (9)(10)(11)(12)(13)(14)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The axis of CXCR4/CXCL12 plays an important role in metastasis of many tumors (9)(10)(11)(12)(13)(14)(22)(23)(24)(25). Abnormal expression of CXCR4 or CXCL12 has been observed in solid tumors such as ovarian cancer (30), rhabdomysarcoma (26), nasopharyngeal carcinoma (21), melanoma (27), colorectal cancer (28), pancreatic cancer (24), and breast cancer (7).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Knaut et al (2005) reported that trigeminal sensory ganglia (TgSG) neurons were ectopically located in the CXC4b morphant zebrafish embryos (embryos injected with morpholine-conjugated antisense oligonucleotides) while both the number of TgSG neurons and axon projections were normal. In CXCR4−/− mice, most GnRH neurons also failed to exit the vomeronasal organ (VNO) at E13, and comparatively few GnRH neurons reached the forebrain (Schwarting GA et al, 2006). Primordial germ cells (PGCs) are the founders of sperm or oocytes.…”
Section: Others-cxcl12/cxcr4mentioning
confidence: 99%